Let the vertices of △ A B C be coinciding with the first, second and fourth vertices of a regular heptagon.
Find tan A + tan B + tan C .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If we write F ( t ) = 1 − t 2 2 t then F ( F ( F ( t ) ) ) − t = − t 8 − 2 8 t 6 + 7 0 t 4 − 2 8 t 2 + 1 t ( 1 + t 2 ) ( t 6 − 2 1 t 4 + 3 5 t 2 − 7 ) and hence the roots of the polynomial G ( t ) = t 6 − 2 1 t 4 + 3 5 t 2 − 7 are tan 7 k π for 1 ≤ k ≤ 6 . Moreover we can write G ( t ) = ( t 3 − 7 t ) 2 − 7 ( t 2 + 1 ) 2 = ( t 3 − 7 t 2 − 7 t − 7 ) ( t 3 + 7 t 2 − 7 t + 7 ) = G 1 ( t ) G 2 ( t ) and we can show that G 1 ( t ) divides the polynomial ( 1 − t 2 ) 3 G 1 ( F ( t ) ) , and that G 2 ( t ) divides ( 1 − t 2 ) 3 G 2 ( F ( t ) ) .
Thus the roots of G ( t ) split into two groups, tan 7 π , tan 7 2 π , tan 7 4 π and tan 7 3 π , tan 7 6 π , tan 7 1 2 π = tan 7 5 π . One set gives the zeroes of G 1 ( t ) , and the other set gives the zeroes of G 2 ( t ) . Thus it follows that tan A + tan B + tan C = tan 7 π + tan 7 2 π + tan 7 4 π must be either 7 or − 7 . Since tan 7 3 π = 1 − tan 7 2 π tan 7 π tan 7 2 π + tan 7 π > tan 7 π + tan 7 2 π it follows that tan A + tan B + tan C = tan 7 π + tan 7 2 π − tan 7 3 π < 0 , so we deduce that the answer is − 7 .
Angle A is 7 3 6 0 d e g r e e s , B is 7 7 2 0 d e g r e e s and C is 7 1 8 0 d e g r e e s . So t a n A + t a n B + t a n C = − √ 7
That doesn't help explain why the answer is − 7 .
Problem Loading...
Note Loading...
Set Loading...
Draw a circle circumscribing the regular heptagon with center O .
As a central angle, ∠ A O B = 7 2 π , and by the inscribed angle theorem ∠ A C B = 7 π . Similarly, ∠ B O C = 7 4 π so ∠ B A C = 7 2 π , and ∠ A O C = 7 8 π so ∠ A B C = 7 4 π . Therefore, the angles of △ A B C are ∠ A = 7 2 π , ∠ B = 7 4 π , and ∠ C = 7 π .
Let x = sin 7 π sin 7 2 π sin 7 4 π and y = cos 7 π cos 7 2 π cos 7 4 π . Then
Therefore, y = cos 7 π cos 7 2 π cos 7 4 π = − 8 1 . Also,
Therefore, x = sin 7 π sin 7 2 π sin 7 4 π = 8 7 .
For any triangle, tan A + tan B + tan C = tan A tan B tan C , so for this triangle,
tan A + tan B + tan C = tan 7 π tan 7 2 π tan 7 4 π = cos 7 π cos 7 2 π cos 7 4 π sin 7 π sin 7 2 π sin 7 4 π = − 8 1 8 7 = − 7 .